Cryopreservation of human lung tissue for 3D ex vivo analysis - Nickolas G. Diodati; Ganlin Qu; Borna Mehrad; Matthew A. Schaller (Respiratory Research)
Abstract Ex vivo culture techniques have assisted researchers in narrowing the translational gap between the lab and the clinic by allowing the study of biology in human tissues. In pulmonary biology, however, the availability of such tissues is a limiting factor in experimental design and constrains the reproducibility and replicability of these models as scientifically rigorous complements to in vitro or in vivo methods. Cryopreservation of human lung tissue is a strategy to address these limitations by generating cryopreserved biobanks of donors in the ex vivo study of pulmonary biology. Modern cryopreservation solutions, incorporating blends of cryoprotective extracellular macromolecules and cell-permeant non-toxic small molecules, have enabled the long-term storage of human lung tissue, allowing repeated experiments in the same donors and the simultaneous study of the same hypothesis across multiple donors, therefore granting the qualities of reproducibility and replicability to ex vivo systems. Specific considerations are required to properly maintain fundamental aspects of tissue structure, properties, and function throughout the cryopreservation process. The examples of existing cryopreservation systems successfully employed to amass cryobanks, and ex vivo culture techniques compatible with cryopreservation, are discussed herein, with the goal of indicating the potential of cryopreservation in ex vivo human lung tissue culture and highlighting opportunities for cryopreservation to expand the utility of ex vivo human lung culture systems in the pursuit of clinically relevant discoveries.